Influence of Integrated Marketing Communications on Female Decision Making in Online Clothing Purchase: A Case Study of Bangkok Metropolis - Thunma, Amornrat; Boonyasana, Kwanruetai (Electronic Journal of Open and Distance Innovative Learning (e-JODIL), 2015)
Selling female clothing online through the use of social networking is now popular and the business has been growing steadily. Social networking is a kind of social media that is easy to access, fast to communicate and cheap in comparison to other competitive media marketing strategies. This study investigated the influence of integrated marketing communications (IMC) on female decision making in online clothing purchases. This quantitative research used a questionnaire in gathering the information. The sample, obtained through quota sampling method, comprised 445 females living in Bangkok and using online social networking services. The results showed that most females viewed the IMC tools (including advertising, public relations, promotion, and direct marketing) as important in making a purchase decision at a moderate level (43.82%). In addition, Eta correlation ratio indicated a non-linear relationship between clothing purchase and the IMC tools, except for advertising that appeared to have a weak positive correlation on the purchase (0.165). The multiple regression analysis found marital status, age, level of education, income, time spent on using the internet, and times to view the products influence the online purchase. The sample suggested the entrepreneurs to give importance to warranties, product information, prices, credibility of the financial transaction, product delivery, and communication channels in order to rise consumers’ need for online purchasing.